ROS and Oxidative Response Systems in Plants Under Biotic and Abiotic Stresses: Revisiting the Crucial Role of Phosphite Triggered Plants Defense Response - Mohammadi, Mohammad Aqa; Cheng, Yan; Aslam, Mohammad; Jakada, Bello Hassan; Wai, Myat Hnin; Ye, Kangzhuo; He, Xiaoxue; Luo, Tiantian; Ye, Li; Dong, Chunxing; Hu, Bin; Priyadarshani, S. V. G. N.; et al. (Frontiers in Microbiology, 2021)
Phosphite (Phi) is a chemical analogue of orthophosphate [(HPO3)2[. It is a systemic fungicide generally known to control the spread of foliar and soilborne Oomycete diseases such as those caused by Phytophthora, Pythium and Plasmopora species. Phi can also control disease symptoms and the spread of pathogenic bacteria, fungi, and nematodes. Phi plays critical roles as a fungicide, pesticide, fertilizer, or biostimulator. Altogether, Phi can reduce the severity of diseases caused by Oomycete, fungi, pathogenic bacteria, and nematodes (leave, stem, fruit, tuber, root, and post-harvest) in various plant species (vegetables, cereals, fruit crops, root/ tuber crops, ornamental and forests). Advance research in molecular, physiological, and biochemical approaches has approved the key role of Phi in improving crop growth, quantity and quality of several plant species. Phi is chemically similar to orthophosphate, and inside the cells, it is likely to interfere with different aspects of phosphate metabolism in both plants and pathogens. In plants, a range of physio-biochemical alterations are induced by plant pathogen stress, which causes lowered photosynthesis activities, enzymatic activities, increased accumulation of reactive oxygen species (ROS), and changes in a large group of genes expressions. To date, several attempts have been made to study plant-pathogen interactions with the intent to minimize the loss of crop productivity. Phi’s emerging function as a biostimulant in plants have boost plant yield and tolerance against various stress factors. This review discusses Phi-mediated biostimulant effects against biotic and abiotic stresses.